2010
DOI: 10.1016/j.bcp.2009.09.020
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage response to the Mdm2 inhibitor Nutlin-3

Abstract: Mdm2 inhibitors represent a promising class of p53 activating compounds that may be useful in cancer treatment and prevention. However, the consequences of pharmacological p53 activation are not entirely clear. We observed that Nutlin-3 triggered a DNA damage response in azoxymethaneinduced mouse AJ02-NM 0 colon cancer cells, characterized by the phosphorylation of H2AX (at Ser-139) and p53 (at Ser-15). The DNA damage response was highest in cells showing robust p53 stabilization, it could be triggered by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 52 publications
5
53
2
Order By: Relevance
“…It should also be noted that in some cellular contexts nutlin-3 treatment of somatic tumor cell lines might have genotoxic effects, as it induces the activation of the DDR and formation of gH2AX foci (Valentine et al, Verma et al, 2010). Although still controversial, such ability seems to be independent of p53 status, and unrelated to the role of nutlin-3 as MDM2 antagonist (Valentine et al, 2011, Verma et al, 2010. Using Flow cytometry, we extended these observations to TGCTs and found that, in the EC cell lines 2102Ep, Tera-1 and NT2D1, though nutlin-3 treatment induced a comparable stabilization of p53 protein (Fig 2A), the magnitude of their apoptotic response was not uniform (Fig.…”
Section: The Role Of P53 In Tgct Response To Treatmentmentioning
confidence: 80%
“…It should also be noted that in some cellular contexts nutlin-3 treatment of somatic tumor cell lines might have genotoxic effects, as it induces the activation of the DDR and formation of gH2AX foci (Valentine et al, Verma et al, 2010). Although still controversial, such ability seems to be independent of p53 status, and unrelated to the role of nutlin-3 as MDM2 antagonist (Valentine et al, 2011, Verma et al, 2010. Using Flow cytometry, we extended these observations to TGCTs and found that, in the EC cell lines 2102Ep, Tera-1 and NT2D1, though nutlin-3 treatment induced a comparable stabilization of p53 protein (Fig 2A), the magnitude of their apoptotic response was not uniform (Fig.…”
Section: The Role Of P53 In Tgct Response To Treatmentmentioning
confidence: 80%
“…Flow Cytometry-HT29 and WI38 were analyzed for DNA content by ethanol fixation and staining with propidium iodide as described previously (19). Floating and adherent cells were combined and analyzed by flow cytometry.…”
Section: Methodsmentioning
confidence: 99%
“…HT29 and HCT116 cells were analyzed for DNA content by ethanol fixation and staining with propidium iodide as previously described. 72 Floating and adherent cells were combined and analyzed by flow cytometry. Adherent cells were harvested using a trypsin-EDTA solution, centrifuged together with the floating cells at 100 × g for 5 min and resuspended in 1 ml of cold saline GM.…”
Section: Discussionmentioning
confidence: 99%